Decision-making in paediatric palliative care interpreting - Contreras-Nourse, Melissa (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
The interpreting profession has long used metaphors or rule statements to describe and teach the ways in which practitioners make decisions (Dean & Pollard, 2011, 2018). Interpreting students are also often taught that the context of an encounter will dictate their decision-making by way of statements such as “it depends”. Such pedagogical statements can make talk between a practitioner and a medical professional about the responsibilities of an interpreter during medical encounters difficult. This study is based on the work of Dean and Pollard (2011, 2018) on value-based decision-making and is guided by the four principles of biomedical ethics (respect for autonomy, non-maleficence, beneficence and justice). It has sought to provide evidence of the existence, applicability and usability of these frameworks through a single case study of a real-life appointment in which a parent of a palliative care outpatient and a medical professional communicated during a consultation, aided by a medical interpreter.